In vitro selection of bacteria with potential for use as probiotics in marine shrimp culture - Vieira, Felipe do Nascimento; Jatobá, Adolfo; Mouriño, José Luiz Pedreira; Vieira, Eduardo Alano; Soares, Mariana; Silva, Bruno Corrêa da; Seiffert, Walter Quadros; Martins, Maurício Laterça; Vinatea, Luis Alejandro (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to isolate strains of lactic acid bacteria with probiotic potential from the digestive tract of marine shrimp (Litopenaeus vannamei), and to carry out in vitro selection based on multiple characters. The ideotype (ideal proposed strain) was defined by the highest averages for the traits maximum growth velocity, final count of viable cells, and inhibition halo against nine freshwater and marine pathogens, and by the lowest averages for the traits duplication time and resistance of strains to NaCl (1.5 and 3%), pH (6, 8, and 9), and biliary salts (5%). Mahalanobis distance (D2) was estimated among the evaluated strains, and the best ones were those with the shortest distances to the ideotype. Ten bacterial strains were isolated and biochemically identified as Lactobacillus plantarum (3), L. brevis (3), Weissella confusa (2), Lactococcus lactis (1), and L. delbrueckii (1). Lactobacillus plantarum strains showed a wide spectrum of action and the largest inhibition halos against pathogens, both Gram‑positive and negative, high growth rate, and tolerance to all evaluated parameters. In relation to ideotype, L. plantarum showed the lowest Mahalanobis (D2) distance, followed by the strains of W. confusa, L. brevis, L. lactis, and L. delbrueckii. Among the analyzed bacterial strains, those of Lactobacillus plantarum have the greatest potential for use as a probiotic for marine shrimp.